The missing link between awareness and the implementation of wetland policy and legislation in communal areas of Zimbabwe - Marambanyika, Thomas (Springer Verlag, 2016)
This paper explores stakeholders’ perceptions of the efficacy of the current policies and legislation meant to conserve wetlands in the communal areas of Zimbabwe. A questionnaire was administered to one hundred and twenty three households adjacent to six wetlands studied including key informants who were interviewed. The existing laws were analysed to determine their appropriateness in light of peoples’ livelihood aspirations and principles of wetland protection. Zimbabwe has no national wetland policy per se but only wetland legislation, however inimitable policies shaped by indigenous tradition and practice were present at each wetland site. The majority of the people were not aware of the existence and rationale of laws governing the conservation of wetlands due to limited awareness education and enforcement by responsible institutions. Therefore, there was a disjuncture between legal provisions and the practical implementation resulting in less impact. Poor implementation of legislation was due to inadequate resources for regulatory agencies, political interference, social conflicts and high incidences of poverty among other factors. The results of the study highlighted that even if awareness was improved, enforcement was likely to remain a challenge unless adequate resources for regulatory institutions and alternative livelihood strategies for communities were availed. The paper thus recommends that development planners should therefore initiate other rural survival options such as restoration of dryland agricultural productivity by introducing water harvesting and conservation farming techniques. This would help to reduce community dependency on already vulnerable wetland ecosystems. Overall, a national wetland policy should be developed through a participatory process, if the legislation is to be used as an effective tool in wetland management.